Human Evolutionary Biology - Muehlenbein, Michael P. (Cambridge : Cambridge University Press, 2010)
Wide-ranging and inclusive, this text provides an invaluable review of an expansive selection of topics in human evolution, variation and adaptability for professionals and students in biological anthropology, evolutionary biology, medical sciences and psychology. The chapters are organized around four broad themes, with sections devoted to phenotypic and genetic variation within and between human populations, reproductive physiology and behavior, growth and development, and human health from evolutionary and ecological perspectives. An introductory section provides readers with the historical, theoretical and methodological foundations needed to understand the more complex ideas presented later. Two hundred discussion questions provide starting points for class debate and assignments to test student understanding.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Human evolution; Human biology; Biological Evolution; Evolution, Molecular; Hominidae